NPR-A regulates self-renewal and pluripotency of embryonic stem cells - Abdelalim, E M (Nature Publishing Group, 2011)
Self-renewal and pluripotency of embryonic stem (ES) cells are maintained by several signaling cascades and by expression of intrinsic factors, such as Oct4, Nanog and Sox2. The mechanism regulating these signaling cascades in ES cells is of great interest. Recently, we have demonstrated that natriuretic peptide receptor A (NPR-A), a specific receptor for atrial and brain natriuretic peptides (ANP and BNP, respectively), is expressed in pre-implantation embryos and in ES cells. Here, we examined whether NPR-A is involved in the maintenance of ES cell pluripotency. RNA interference-mediated knockdown of NPR-A resulted in phenotypic changes, indicative of differentiation, downregulation of pluripotency factors (such as Oct4, Nanog and Sox2) and upregulation of differentiation genes. NPR-A knockdown also resulted in a marked downregulation of phosphorylated Akt. Furthermore, NPR-A knockdown induced accumulation of ES cells in the G1 phase of the cell cycle. Interestingly, we found that ANP was expressed in self-renewing ES cells, whereas its level was reduced after ES cell differentiation. Treatment of ES cells with ANP upregulated the expression of Oct4, Nanog and phosphorylated Akt, and this upregulation depended on NPR-A signaling, because it was completely reversed by pretreatment with either an NPR-A antagonist or a cGMP-dependent protein kinase inhibitor. These findings provide a novel role for NPR-A in the maintenance of self-renewal and pluripotency of ES cells.